Sejarah Penyebaran Agama Islam di Wilayah Kecamatan Sukadana Kabupaten Ciamis Provinsi Jawa Barat - Ahmad Rizky Fauzi; Hasni Hasan (Badan Riset dan Inovasi Nasional (BRIN), 2024)
Sukadana is one of the sub-districts in Ciamis Regency. Majority of Sukadana District residents are Muslim. The large number of adherents of Islam in the Sukadana District area cannot be separated from the role of the ulama and the appropriate Islamization process at that time. There has never been a study regarding the spread of Islam in the area that is now Sukadana District. Based on this background, the problem that will be discussed is who the figures who spread Islam in Sukadana District were, where they came from and how they spread it. The research uses historical methodology. Data collection techniques include collecting historical sources, both primary and secondary, then heuristics and criticism. The spread of Islam in the Sukadana District area was carried out smoothly and did not eliminate the traditions of the previous religion. There are around 45 figures who spread Islam and they first entered the Sukadana District area in the 16th century or around 1500-1600 AD. The spread of Islam in the Sukadana District area was carried out smoothly and did not eliminate the traditions of the previous religion. This study can be a lesson in the fields of politics, archaeology, history and religion.